The creation of social norms under weak institutions - Diekert, Florian; Eymess, Tillmann; Luomba, Joseph; Waichman, Israel (Journal of the Association of Environmental and Resource Economists, 2022)
Formal regulations often fail to ensure sustainable management of natural resources. An alternative approach could rely on the interaction of norm-based interventions and social sanctions. Our lab-in-the-field experiment with fishermen at Lake Victoria studies how a norm-based intervention, namely, social information about high or low levels of previous cooperation, affects behavior and beliefs in a prisoner’s dilemma game with or without weak social sanctioning. Providing different social information succeeds in creating different norms of cooperation, but only if sanctioning is possible: cooperation rates start at a high level and stay at a high level when social information emphasizes cooperation but start at a low level and stay at a low level when social information emphasizes defection. Without social sanctioning, cooperation rates decline, irrespective of the social information. Particularly participants with close connection to others in their experimental session conform to the behavior that is emphasized by the social information message under sanctioning.